2018
DOI: 10.1093/jscr/rjy318
|View full text |Cite
|
Sign up to set email alerts
|

Transmesenteric hernia with two mesenteric defects in an adult

Abstract: Transmesenteric hernia is a rare cause of small bowel strangulation in adults and, to our knowledge, no one has reported the existence of two mesenteric defects in an adult. Our patient was a 73-year-old Japanese woman who presented to our emergency department complaining of abdominal pain and nausea. Computed tomography with contrast enhancement revealed a closed loop obstruction in the pelvis, suggesting small bowel strangulation due to an internal hernia. The emergency exploratory laparotomy indicated a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…10,12,13 Transmesenteric hernias can be through small bowel mesentery which is more common in children or through the transverse colon mesentery. 12,14 In the index case, the small bowel was herniated through a defect in the transverse colon without the mesenteric sac which was rare compared to herniation through small bowel mesentery. 15 A high index of clinical suspicion is required for internal hernias when there are no signs of inguinal hernia or a history of previous abdominal surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,13 Transmesenteric hernias can be through small bowel mesentery which is more common in children or through the transverse colon mesentery. 12,14 In the index case, the small bowel was herniated through a defect in the transverse colon without the mesenteric sac which was rare compared to herniation through small bowel mesentery. 15 A high index of clinical suspicion is required for internal hernias when there are no signs of inguinal hernia or a history of previous abdominal surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis is uncertain. Treves in 1885, emphasized the weakest area in terminal ileum mesentery circumscribed by the ileocolic artery and its last ileal branch 7,8 . Another study found prenatal intestinal ischemia leads to thinning of the mesenteric leaves associated with bowel atresia in 5.5% of cases 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Korn et al [13] reported complete omental resection in a patient with Swiss cheese omentum containing multiple defects of varying size. In contrast, Cao et al [14] reported the closure of multiple mesenteric defects to preserve the omentum and thus prevent adhesional bowel obstruction.…”
Section: Discussionmentioning
confidence: 99%